Comportamento de nabo forrageiro (Raphanus sativus L.) e nabiça (Raphanus raphanistrum L.) em diferentes sistemas de manejo do solo - Piffer, Cássio Roberto [UNESP]; Benez, Sergio Hugo [UNESP]; Bertolini, Erick Vinicius [UNESP] (My University, 2010)
This work aimed to evaluate the performance of Raphanus sativus L. and Raphanus raphanistrum L. through three soil tillage systems. The experiment was carried out at the Lageado Experimental Farm, “Faculdade de Ciências Agronômicas”, UNESP, Botucatu campus, from February to October, 2005 in Distroferic Red Nitrosoil; which has been cultivated for nine years under the same soil tillage systems. The experimental design was carried out in randomized blocks with split-plots and four repetitions; plots were made up by soil tillage systems (conventional tillage, minimum tillage and no-tillage) and split-plots were made up by winter crops (Raphanus sativus L. and Raphanus raphanistrum L.). Data were analyzed by the Tukey test at 5% probability for means comparisons. Raphanus sativus L. keeps high capacity to produce dry matter, assuring its feasibility for soil vegetal production during winter time. Raphanus raphanistrum L. grains showed high oil content making it possible the extraction for biodiesel production. Soil tillage systems showed statistical differences in most production components of Raphanus sativus L. and Raphanus raphanistrum L., being conventional and minimum tillage more productive compared to no-tillage.

O presente trabalho teve como finalidade avaliar o desempenho de nabo forrageiro e nabiça em três sistemas de manejo do solo. O experimento foi conduzido no período compreendido entre fevereiro e outubro de 2005, na Fazenda Experimental Lageado, da Faculdade de Ciências Agronô- micas da UNESP, Campus de Botucatu - SP, em NITOSSOLO VERMELHO Distroférrico, cultivado há nove anos com os mesmos sistemas de manejo do solo. O delineamento experimental utilizado foi de blocos ao acaso com parcelas subdivididas e quatro repetições, sendo as parcelas constituídas pelos sistemas de manejo do solo (preparo convencional, cultivo mínimo e plantio direto) e as subparcelas pelas culturas de inverno (nabo forrageiro e nabiça). Os dados obtidos foram submetidos à análise de variância com teste de Tukey a 5 % de probabilidade para comparar as médias. O nabo forrageiro tem alta capacidade de produzir massa seca, confirmando sua viabilidade para produção de cobertura vegetal do solo durante o inverno. Os grãos de nabiça apresentaram consideráveis teores de óleo, podendo ser cultivada com o propósito de extração para produção de biodiesel. Nos sistemas de manejo do solo ocorreram diferenças estatísticas na maioria dos componentes de produção das culturas de nabo forrageiro e nabiça, sendo que o preparo convencional e o cultivo mínimo foram mais produtivos, em relação ao plantio direto.
Performance of Raphanus sativus L. and Raphanus raphanistrum L. under different soil tillage systems
Keywords: Raphanus sativus; Raphanus raphanistrum; Soil tillage; Raphanus sativus; Raphanus raphanistrum; Preparo do solo